Acknowledgment to Reviewers of Infrastructures in 2020 - Infrastructures Editorial Office (Infrastructures, 2021)
Peer review is the driving force of journal development, and reviewers are gatekeepers who ensure that Infrastructures maintains its standards for the high quality of its published papers [...]